2022
DOI: 10.1186/s12989-022-00492-9
|View full text |Cite
|
Sign up to set email alerts
|

Coronas of micro/nano plastics: a key determinant in their risk assessments

Abstract: As an emerging pollutant in the life cycle of plastic products, micro/nanoplastics (M/NPs) are increasingly being released into the natural environment. Substantial concerns have been raised regarding the environmental and health impacts of M/NPs. Although diverse M/NPs have been detected in natural environment, most of them display two similar features, i.e.,high surface area and strong binding affinity, which enable extensive interactions between M/NPs and surrounding substances. This results in the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 266 publications
0
50
0
Order By: Relevance
“…The biological fate of nanomaterials is largely determined by their morphology and surface corona. 60 For instance, the comparison of MoS 2 biodistribution in transgenic mice with fibrinogen (Fg), apolipoprotein E (ApoE), immunoglobulin M (IgM), or complement 3 (C3) deficiency provides convincing support that ApoE binding on MoS 2 nanosheets dictates their accumulation in liver sinusoid and splenic red pulp. 61,62 In this study, 12 apolipoproteins were identified in the 320 corona proteins of FeNGR (Table S6).…”
Section: ■ Discussionmentioning
confidence: 99%
“…The biological fate of nanomaterials is largely determined by their morphology and surface corona. 60 For instance, the comparison of MoS 2 biodistribution in transgenic mice with fibrinogen (Fg), apolipoprotein E (ApoE), immunoglobulin M (IgM), or complement 3 (C3) deficiency provides convincing support that ApoE binding on MoS 2 nanosheets dictates their accumulation in liver sinusoid and splenic red pulp. 61,62 In this study, 12 apolipoproteins were identified in the 320 corona proteins of FeNGR (Table S6).…”
Section: ■ Discussionmentioning
confidence: 99%
“…proteins, lipids and carbohydrates, that adhere to the particles' surface (Docter et al, 2015). As the adherence of these macromolecules will change the surface properties of the particles and therefore their interaction with biological systems (Monopoli et al, 2012;Cao et al, 2022), the possible role of the corona has to be considered during in vitro testing (Allen et al, 2006). For example, Abdelkhaliq et al (2018) analyzed the protein corona on different PS nanoplastics via LC-MS/MS and reported differences based on the surface modification of the particles, which in turn impacted the uptake rates of the nanoplastics.…”
Section: Challenges and Considerations When Testing Plastic Particles...mentioning
confidence: 99%
“…MNPs absorb proteins from the body and form protein coronas (Treuel et al, 2014). Unlike MNPs that are exposed, those that react with cells are generally already enveloped by a protein corona (Cao et al, 2022), further modifying the properties of MNPs (Tenzer et al, 2013), and causing cellular interactions and enhanced toxicity (Nasser & Lynch, 2016). MNPs of PS easily permeate lipid bilayer membranes, inducing alterations in membrane structure and eventually affecting cell function (Rossi et al, 2014).…”
Section: Cellular Interactionmentioning
confidence: 99%